On the periphery of a Barbarian Empire? British travellers in the Duchy of Warsaw and the Kingdom of Poland in the years 1813–1915 - Deles, Przemysław (The British Empire: Interdisciplinary Deliberations, 2019)
From the time the Russian army entered the Polish territory in pursuit of Napoleon’s retreating forces, up to the period when the Russians withdrew from Warsaw in the wake of advancing German troops during the First World War, more than one hundred travellers from the British Isles documented their experiences in Poland under the Russian Partition in books and articles. These visitors included Arthur Wellesley, 1st Duke of Wellington, and Charles Dodgson—better known as Lewis Carroll. At the beginning of the period in question, most travellers were poorly prepared for visiting Poland. Because of the limited number of publications available on the market, the travellers were forced to read each other’s accounts, and they commented on their fellow travellers’ observations. With time, the situation improved greatly, but still the image of the Poles and their country was saddled with stereotypes. Poland was seen as being a partly barbaric country belonging to the semi-oriental peripheries of Europe that lay on the border with Asia. The material presented in this text by no means includes all the accounts written by the British and Irish travellers to Poland at a time when it was under the Russian partition; however, it is believed to be a valid introduction to a more in-depth study of travellers’ descriptions of their experiences in Poland.